In the winning mood: Affect in the Iowa gambling task - Marieke de Vries; Rob W. Holland; Cilia L. M. Witteman; Gisela Böhm; Wibecke Brun (Judgment and Decision Making, 2008)
The present research aimed to test the role of mood in the Iowa Gambling Task (IGT; Bechara et al., 1994). In the IGT, participants can win or lose money by picking cards from four different decks. They have to learn by experience that two decks are overall advantageous and two decks are overall disadvantageous. Previous studies have shown that at an early stage in this card-game, players begin to display a tendency towards the advantageous decks. Subsequent research suggested that at this stage, people base their decisions on conscious gut feelings (Wagar & Dixon, 2006). Based on empirical evidence for the relation between mood and cognitive processing-styles, we expected and consistently found that, compared to a negative mood state, reported and induced positive mood states increased this early tendency towards advantageous decks. Our results provide support for the idea that a positive mood causes stronger reliance on affective signals in decision-making than a negative mood.